ANALISIS PENGARUH FAKTOR FUNDAMENTAL EKONOMI MAKRO DAN HARGA MINYAK TERHADAP SAHAM LQ45 DALAM JANGKA PENDEK DAN JANGKA PANJANG - Dwi Wahyu Prasetiono (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
The objective of this research was to examine the macro economics factors and theprice of crude oil that influencing LQ45 stock price in the short and long run. Therewere four fundemntal macro economics variabel in this study such as economic growth,SBI rate, and exchange rate wich used with crude oil price to examine their influenceto LQ45 Stock price. Â This study used Error Correction Model to analyse the prob-lem. The result show that in the short run, economic growth and crude oil price haveinfluence to LQ45 stock price. Furthermore, in the long run economic groth, SBI ratehave influence to LQ45 stock price.Keywords: LQ45 stock price, macro economics variables, crude oil, and ECM